2011
DOI: 10.1111/j.1600-0609.2011.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in adult patients with primary immune thrombocytopenia

Abstract: Fatigue is a common symptom among patients with ITP. These data provide the basis for future studies to define the clinical importance of fatigue in ITP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 40 publications
9
104
2
5
Order By: Relevance
“…Additionally, patients with lower WHO bleeding scores reported higher HRQoL scores as measured using the SF-36v2, the FACIT-Fatigue, and the FACT-Th6 instruments. This is consistent with a recent study demonstrating an association between fatigue and the presence of bleeding symptoms 21 . It is not known if these correlations would permit the use of a simpler scale to assess and monitor bleeding in patients with chronic ITP in the clinic; however, these correlations further support the accuracy and sufficiency of the simpler WHO Bleeding Scale to assess and monitor bleeding and bruising in adult patients with chronic ITP.…”
Section: Who Bleeding Scalesupporting
confidence: 93%
“…Additionally, patients with lower WHO bleeding scores reported higher HRQoL scores as measured using the SF-36v2, the FACIT-Fatigue, and the FACT-Th6 instruments. This is consistent with a recent study demonstrating an association between fatigue and the presence of bleeding symptoms 21 . It is not known if these correlations would permit the use of a simpler scale to assess and monitor bleeding in patients with chronic ITP in the clinic; however, these correlations further support the accuracy and sufficiency of the simpler WHO Bleeding Scale to assess and monitor bleeding and bruising in adult patients with chronic ITP.…”
Section: Who Bleeding Scalesupporting
confidence: 93%
“…Almost 70% of patients ( n = 25) suffered from fatigue, with only one control indicating such. One study investigating fatigue in adult primary AITP highlighted the clinical importance of this symptom [43]. In accordance with the findings of this study, chronic fatigue syndrome (CFS) occurs four times more frequently in women than in men, with CFS patients demonstrating signs of OS [44].…”
Section: Discussionsupporting
confidence: 83%
“…For example, fatigue is now a well-characterized phenomenon in ITP. We and others [17,18,19] have observed that fatigue predominantly occurs when platelet counts decrease to < 50,000/µl in most affected patients. Comparison of adverse reactions in patients either receiving drugs or a placebo has demonstrated that the difference between both groups is insignificant.…”
Section: Discussionmentioning
confidence: 90%